2021
DOI: 10.1371/journal.pone.0245072
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of multi epitope-based subunit vaccine by exploring MERS-COV proteome: Reverse vaccinology and molecular docking approach

Abstract: Middle East respiratory syndrome (MERS-COV), first identified in Saudi Arabia, was caused by a novel strain of coronavirus. Outbreaks were recorded from different regions of the world, especially South Korea and the Middle East, and were correlated with a 35% mortality rate. MERS-COV is a single-stranded, positive RNA virus that reaches the host by binding to the receptor of dipeptidyl-peptides. Because of the unavailability of the vaccine available for the protection from MERS-COV infection, the rapid case de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 70 publications
(83 reference statements)
1
18
0
Order By: Relevance
“…The root mean square fluctuation (RMSF) for all atoms of the HMG-CoA reductase-ginger extracts complex shows fluctuations within 0.1–1.2nm. In line with previous studies RMSF is an important parameter that yields data about the structural adaptability of Cα atoms of every residue in the system [29 30 31 35] . RMSF shows the fluctuation of terminal amino acids between 250-446aa, which is consistence with previous study [15] .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The root mean square fluctuation (RMSF) for all atoms of the HMG-CoA reductase-ginger extracts complex shows fluctuations within 0.1–1.2nm. In line with previous studies RMSF is an important parameter that yields data about the structural adaptability of Cα atoms of every residue in the system [29 30 31 35] . RMSF shows the fluctuation of terminal amino acids between 250-446aa, which is consistence with previous study [15] .…”
Section: Discussionsupporting
confidence: 69%
“…But, few study reported a comparison of simvastatin efficacy with ginger rhizome extract to show similarity and difference amongst the two to manage dyslipidemia. At the present time, several studies have been revealed the significant out of using computational approaches to investigate small molecules-target interactions [29 30 31 32 33] . In this study, we applied molecular docking, molecular dynamics (MD) simulations, and other computer aided drug design (CADD) methods to study HMG-CoA reductase and ginger extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the appropriateness of using a predicted structure for rational design, a previous validation study of I-TASSER on de novo protein design of 87 proteins showed that I-TASSER could accurately fold the designed sequences with an average root mean square deviation (RMSD) of 2.1Å (Mitra et al, 2013). Previous studies have also used I-TASSER for rationally designing stability into a variety of proteins (Wan et al, 2019;Guo et al, 2019;Ashfaq et al, 2021). Still, the resolution of the model is a key limitation on the success rate of the designed screen whereby inaccurately estimated surface exposure of asparagine and glutamine residues or the Cα distance of neighboring cysteines directly affects the prediction of supercharging or de novo disulfide mutations respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several strategies for developing and designing competent and effective next-generation multi-epitope vaccines based on immunoinformatics approaches are readily available [70]. Previously, immunoinformaticsbased approaches have been employed to propose efficient multi epitope vaccine candidates for Lassa virus [71], Zika Virus [46], Dengue virus [72], influenza virus [73], Middle East Respiratory Syndrome-Coronavirus (MERS-CoV) virus [74,75], Respiratory Syncytial Virus [76], Severe Acute Respiratory Syndrome-Coronavirus 2 (SARS-CoV-2) [77][78][79], chikungunya virus (CHIKV) [80] and many others. Because of the enormously reported merits and wide acceptability we adopted immunoinformatics-based approaches to de-sign an effective vaccine candidate against Pakistani-based HCV subtype-3a that could efficiently enhance immune response after vaccination.…”
Section: Discussionmentioning
confidence: 99%